Penerapan Metode Talaqqi Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Peserta Didik Pada Mata Pelajaran Pai Kelas XI.3 Di SMA N 6 Luwu Timur: Penelitian Tindakan Kelas - Awal Parubak; M Yunus Anwar; Abdul Wahab; Abdul Qahar Zainal; Mustamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This Classroom Action Research (CAR) examines the effectiveness of the Talaqqi method in improving the ability to read the Qur'an of class XI.3 students of SMA Negeri 6 Luwu Timur. This method is applied in two cycles, including planning, implementation, observation, and reflection. The results show a significant increase. From the pre-cycle to cycle I, there was an increase of 34.28%, and from cycle I to cycle II, the increase reached 22.86%. The average score of students also increased significantly, namely 10.8 points in cycle I and 16.86 points in cycle II. These data show a positive impact of the Talaqqimethod on students' ability to read the Qur'an. In conclusion, the Talaqqi method has proven to be effective. This study recommends the application of this method in Islamic Religious Education learning to optimize students' Qur'an reading skills. The substantial increase in students' reading ability and average score is strong evidence of the success of this method. Further research can be conducted to examine the application of the Talaqqi method in different age groups and ability levels.